Quand le supportérisme et la politique s’imbriquent - Gökçe Tuncel (European Journal of Turkish Studies)
In 2010 a few ultras from Çarşı, a well known fan group of the Beşiktaş football club, formed the Beleştepe (“Free hill” in English) in order to develop collective action against capitalist and industrial football. The name of this group comes from a hill next to the İnönü stadium. From this hill, it is possible to see 70% of the inside of the stadium and fans who do not have enough money to buy a ticket settle on this hill to watch the match. But above all, their decision to gather in a separate group came from their political position, which is more explicit and precise than that of Çarşı. This article will analyse different modes of politization of the two groups.